2020
DOI: 10.7307/ptt.v32i4.3303
|View full text |Cite
|
Sign up to set email alerts
|

Phase Fluctuation Analysis in Functional Brain Networks of Scaling EEG for Driver Fatigue Detection

Abstract: The characterization of complex patterns arising from electroencephalogram (EEG) is an important problem with significant applications in identifying different mental states. Based on the operational EEG of drivers, a method is proposed to characterize and distinguish different EEG patterns. The EEG measurements from seven professional taxi drivers were collected under different states. The phase characterization method was used to calculate the instantaneous phase from the EEG measurements. Then, the optimiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…They concluded that combining the MST approach with the SL approach improved the classification accuracy of all the classifiers used in the study, especially the KNN classifier [27]. Some researchers used the phase characterisation method to calculate the instantaneous phase of EEG signals, optimised the EEG signal data by spatial model analysis, and demonstrated the method's effectiveness [28]. Some researchers used Partial Directed Coherence (PDC) to calculate the correlation between EEG channels and used SVM as a classifier for the critical EEG electrodes and frequency bands for fatigue driving detection and obtained the conclusion that the low-frequency bands were better identified than the high-frequency bands.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that combining the MST approach with the SL approach improved the classification accuracy of all the classifiers used in the study, especially the KNN classifier [27]. Some researchers used the phase characterisation method to calculate the instantaneous phase of EEG signals, optimised the EEG signal data by spatial model analysis, and demonstrated the method's effectiveness [28]. Some researchers used Partial Directed Coherence (PDC) to calculate the correlation between EEG channels and used SVM as a classifier for the critical EEG electrodes and frequency bands for fatigue driving detection and obtained the conclusion that the low-frequency bands were better identified than the high-frequency bands.…”
Section: Related Workmentioning
confidence: 99%
“…Functional brain network [27][28][29][30][31][32] describes the statistically significant connection relationship between the nodes of the brain network, does not reflect the causal relationship between the nodes, and is an undirected network. It is based on the electromagnetic signal and kinetic signal of the brain network etc.…”
Section: The Construction Of Brain Functional Networkmentioning
confidence: 99%